Uprość wyrażenia algebraiczne.
a) 4x + 5 - x - 4 + x - 3x =
b) 0,5a - 2a + 9 - 0,5a - 11,5 =
c) -14k + 9k - 13 + k + 3 + 4k =
d) -3k + 2m + 5m - 7 + k - m =
e) 2x - 4 + 3x - 2 =
f) x - 3y - 2x + 6y
g) 2y - 5 - 3y - 4 - 8y + 9 =

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T19:00:54+01:00
A) 4x + 5 - x - 4 + x - 3x = x + 1
b) 0,5a - 2a + 9 - 0,5a - 11,5 = - 2a - 2,5
c) -14k + 9k - 13 + k + 3 + 4k = - 10
d) -3k + 2m + 5m - 7 + k - m = - 2k + 6m - 7
e) 2x - 4 + 3x - 2 = 5x - 6
f) x - 3y - 2x + 6y = - 1x + 3y
g) 2y - 5 - 3y - 4 - 8y + 9 = - 9y
4 5 4
2010-03-10T19:01:21+01:00
A. 4x + 5 - x - 4 + x - 3x = x + 1
b. 0,5a - 2a + 9 - 0,5a - 11,5 = -2a + 2,5
c.-14k + 9k - 13 + k + 3 + 4k = 10k - 10
d. -3k + 2m + 5m - 7 + k - m = 2k + 6m
e.2x - 4 + 3x - 2 = 5x - 6
f. x - 3y - 2x + 6y = -x + 3y
g. 2y - 5 - 3y - 4 - 8y + 9 = -9y + 0


liczę na naj ;)
1 2 1
2010-03-10T19:05:21+01:00
A) 4x + 5 - x - 4 + x - 3x = x +1
b) 0,5a - 2a + 9 - 0,5a - 11,5 = -2a -2,5
c) -14k + 9k - 13 + k + 3 + 4k = -10
d) -3k + 2m + 5m - 7 + k - m = -2k +6m -7
e) 2x - 4 + 3x - 2 = 5x-6
f) x - 3y - 2x + 6y= -x+3y
g) 2y - 5 - 3y - 4 - 8y + 9 = -9y
2 5 2